Sponges as a complement of sedimentary facies analysis in island deposits of Upper Paraná River. (November 2017) - Zviejkovski, I.P.; Stevaux, J.C.; Leli, I.T.; Parolin, M.; Campos, J.B.
Abstract: This paper shows the importance of the sponge spicules as complement of sedimentary facies analysis in order to reconstruct the hydrach stages involved in island formation in the Upper Paraná River, Brazil. River in the study reach is anabranching with islands of different sizes covered by typical alluvial forest. We noted that the sponge spicules communities vary according to the changes in the environments involved in the island formation processes. The sponges were identified by their microscleres and gemoscleres in optical microscope as Metania spinata, Oncosclera navicella, Oncosclera jewelli, and possibly the genus Corvoheteromeyenia sp. (Ezcurra de Drago, 1979). By correlating the information coming from the sponges and sedimentary facies, it was possible to identify five phases of the island construction and their respective hydrach stages: 1) bar-island channel (Eupotamic stage), 2) blind channel (Parapotamic stage), 3) lake, 4) swamp (both Paleopotamic stage), and 5) forested island (Terrestrial stage). Using 14 C dating and rate of sedimentation, we observed that the development of these five phases took ∼900–1000 years. The data also supported the idea that the forest begin to be formed 134–160 years ago. We concluded that sponge is a strong tool on paleoenvironmetal reconstruction when used with another indicators (in this case the facies analysis) and can be applied other fluvial studies as river management especially for long-term impacted systems (by dams) as those of the Paraná River Basin. Highlights: Use of sponge as bioindicators to understand the evolutionary stages of river island formation. Integration of biologic indicators as a complement of sedimentary facies analysis. Sponge spicules in sediment used for definition of the hydrach stages. Relationship between sedimentary processes and rates of forest colonization.